Risk of structural failure in concrete sewers due to internal corrosion. (August 2016) - Kuliczkowska, Emilia
Abstract: The purpose of the investigations was to find out the frequency of internal corrosion occurrence in concrete sewers, the thickness of corroded walls, and to develop the method of determining the risk of structural failure due to corroded pipes. The data on corroded concrete pipes were collected in CCTV (Closed Circuit Television) surveys performed at the Kielce University of Technology. The surveys covered the total of > 14 km of concrete sewers operating in numerous locations in Poland's cities and towns. The frequency and the thicknesses of corroded pipes in sanitary, stormwater and combined sewers were established. The sewers, in which corrosion was observed, were classified into the proposed categories of structural failure probability which differed in sewer wall loss relative to the full thickness of the sewer wall. Additionally, the method was proposed for determining the category of failure consequences and the risk of sewer failure due to internal corrosion. The results of surveys showed that, like in other countries, also in Poland, internal corrosion in concrete sewer poses a serious structural hazard to their safety. The proposed method gives an important tool that allows a proper management of sewer systems constructed from concrete pipes. The method makes it possible to eliminate, or significantly to reduce structural risk caused by internal corrosion in concrete sewers which can be done by scheduled CCTV surveys of sewers and trenchless renewal performed according to plans developed in advance. Highlights: Magnitude and frequency of internal corrosion in concrete sewers were determined. Methods of risk evaluation for sewer systems were analysed. Categories of probability of internal corrosion for concrete sewers were proposed. Method of the risk assessment of structural failure was proposed.